Alawism in the novel “The Martyr of Love’’ - Karakaş, Rezan; Beyhan, Derviş (Journal of Alevism-Bektashism Studies, 2017)
Some cultures and beliefs of Alawism are included in the novel in which the Most Revered Huseyin’s adventure finished with shadada. Especially, worshipping, whirlling, fellowship, the Most Revered Ali, the household of the Prophet Muhammad, the leadership and calling come to the forefront, invocation and day of ashura. The factors which have importance in the culture of today’s Alewism were explained as a novel art in the novel ‘The Martyr of Love’ which is a historical novel.The factors of Alawism take the attention of the reader, expand the view of the reader and these factors also conclude the main event of the story. The writer make the scene colourful which he created in the reader’s mind. By knowing about the beliefs, rituals, traditions, motifs which are used both in today’s Alewism culture and in the novel make the opus to understand holistically. Turgut makes the Kerbela Incident clear from the view of literature and figures ideally true tragic life experience by getting help from the varied culture factors.
Keywords: Ahmet Turgut; Most Revered Huseyin; Alawism; The Prophet Ali; fellowship; worshipping; whirlling